Psychological interventions for behavioral adjustments in diabetes care - a value-based approach to disease control - Chew, Boon How; Fernandez, Aaron; Shariff Ghazali, Sazlina (Dove Medical Press, 2018)
Psychological aspects of a person, such as the personal value and belief systems, cognition and emotion, form the basis of human health behaviors, which, in turn, influence self-management, self-efficacy, quality of life, disease control and clinical outcomes in people with chronic diseases such as diabetes mellitus. However, psychological, psychosocial and behavioral interventions aimed at these groups of patients have yielded inconsistent effects in terms of clinical outcomes in clinical trials. This might have been due to differing conceptualization of health behavioral theories and models in the interventions. Assimilating different theories of human behavior, this narrative review attempts to demonstrate the potential modulatory effects of intrinsic values on cognitive and affective health-directed interventions. Interventions that utilize modification of cognition alone via education or that focuses on both cognitive and emotional levels are hardly adequate to initiate health-seeking behavior and much less to sustain them. People who are aware of their own personal values and purpose in life would be more motivated to practice good health-related behavior and persevere in them.